Numerical simulation of strong katabatic winds at Syowa and Mizuho Station, Antarctica - Adachi, Takashi (1983)
P(論文) The vertical profiles of the wind speed and air temperature and the wind spiral are studied in the case of the typical strong katabatic wind observed by radiosondes at Syowa and Mizuho Stations, Antarctica. The vertical profiles of the two horizontal wind components, eddy diffusivity, shear stress and local value of Monin-Obukhov length are calculated with the numerical model of the katabatic winds developed by ADACHI (Nankyoku Shiryo, 67,64,1979). The numerical solutions of the katabatic wind profiles agree well with the observed ones at Syowa Station. departmental bulletin paper